The innovator's dilemma : - Clayton M. Christensen (Mass Harvard Business School Press, 2016)
The bestselling classic on disruptive innovation, by renowned author Clayton M. Christensen. His work is cited by the world’s best-known thought leaders, from Steve Jobs to Malcolm Gladwell. In this classic bestseller—one of the most influential business books of all time—innovation expert Clayton Christensen shows how even the most outstanding companies can do everything right—yet still lose market leadership.